A responsabilidade civil do estado pela paralisação nas atividades essenciais - Vezzoni, Marina Rosa (2005)
ABSTRACT This study has as objective to analyze the interruption of the essential activities resulting from the celetista (labor contracts as per the CLT Labor Laws Consolidation) labor relationships, being the employer either the government or the free enterprise, specially regarding the civil liability of the co-participants in the negotiation process. The State, by the way, shall be the main active player and the focus on the examination of the civil liability in terms of activity risk perspectives, that is, objectively, regarding the commissive or ommissive behavior. In order to reach this conclusion, it shall be considered the juridical nature of the strike, mainly facing the considerations regarding the limitation of the coalition right, emphasizing, based on the Comparative Law, the obligation of keeping the minimum activities, and the consequent sanctions due to the losses resulting from the total interruption of the services, which is contrary to the rights of the community. This is justified, as the said services interruption becomes increasingly recurrent, because the Government, able to act also through the Judiciary, equipped with the normative system for that, is negligent, and the community, astonished, stays as the spectator of the conclusion of this negligence scenario. The focus of the research is dogmatic. The approach method used is systemic, together with an auxiliary comparative method and the indirect documentation technique, by means of bibliographic research.